A green-synthesized phosphorescent carbon dot composite for multilevel anti-counterfeiting. Issue 15 (6th July 2021) - Jiang, Wenjie; Liu, Lan; Wu, Yueyue; Zhang, Peng; Li, Feiyang; Liu, Juqing; Zhao, Jianfeng; Huo, Fengwei; Zhao, Qiang; Huang, Wei
Abstract : A green-synthesized nanocarbon phosphorescent material was applied to multilevel anti-counterfeiting fields, with ultra-long phosphorescence lifetime and humidity sensitivity. Abstract : Room temperature phosphorescent (RTP) materials are rising and gaining considerable attention due to their special photo-capture–release ability. Herein, a kind of environmentally friendly RTP composite was devised by microwaving a mixture of carbon dots, boric acid, and urea, in the presence of covalent bonds and hydrogen bonds between each of the components. The resultant RTP material showed ultra-long phosphorescence lifetime up to 1005.6 ms with an outstanding afterglow as long as 9.0 s. Moreover, this afterglow feature with moisture sensitive behavior was explored to achieve multilevel anti-counterfeiting, with the function of complex decryption of encrypted secret information under multiple stimuli. Our results provide a green strategy for scalable synthesis of carbon-based RTP materials, and extend their application scope to high level information security.